Management of Engineering Colleges - Wakhlu, O. N. (Journal of Engineering Education Transformations, 1996)
The paper gives some ideas on the management of engineering colleges and similar technical institutions which perform the important task of educating and training professional engineers for a rapidly developing country. Attention has been focused on some vital issues and an insight provided on how these can be dealt with. The procedures discussed are based on author's long and varied experience in technical education in the country and abroad.